2005
DOI: 10.1091/mbc.e05-05-0434
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofHistoplasma capsulatumTranscripts Induced in Response to Reactive Nitrogen Species

Abstract: The pathogenic fungus Histoplasma capsulatum escapes innate immune defenses and colonizes host macrophages during infection. After the onset of adaptive immunity, the production of the antimicrobial effector nitric oxide ( ⅐ NO) restricts H. capsulatum replication. However, H. capsulatum can establish persistent infections, indicating that it survives in the host despite exposure to reactive nitrogen species (RNS). To understand how H. capsulatum responds to RNS, we determined the transcriptional profile of H.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
74
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 86 publications
1
74
0
1
Order By: Relevance
“…P450nor is therefore a multi-functional detoxifying enzyme. P450nor is also related to the pathogenicity of a fungus [48].…”
Section: Discussionmentioning
confidence: 99%
“…P450nor is therefore a multi-functional detoxifying enzyme. P450nor is also related to the pathogenicity of a fungus [48].…”
Section: Discussionmentioning
confidence: 99%
“…No functions for PBG-D in the RNS response have been reported on the basis of the transcriptomes of S. cerevisiae, C. albicans, and H. capsulatum (6,14,17,25). This might be due to the relatively lower induction level of hemC transcription by RNS than of the genes characterized by the transcriptome analyses.…”
Section: Discussionmentioning
confidence: 92%
“…The synthesized protoheme serves as a cofactor for FHb and enables RNS tolerance, which implies that hemC responds to RNS and regulates protoheme synthesis for adaptation to nitrosative stress conditions. Reports have shown that RNS also induce the expression of genes for some fungal hemoproteins, including catalases and peroxidases, which facilitate tolerance of the oxidative stress caused by RNS (22,25). The A. nidulans isozymes respond to and facilitate the tolerance of oxidative stress (13,18), although their role in the RNS response remains obscure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations